Prosthetic joint infection: state-of-the-art - Boris Sergeyevich Belov (Современная ревматология, 2013)
In current clinical practice, joint replacement is one of the progressive and permanently developed surgical treatments in patients with locomotor injury of any genesis. However, the upward trend in the number of replacements is inevitably accompanied by the rising number of patients with periprosthetic joint infection. The polymorphism of its clinical picture and the nonspecificity of diagnostic tests lead to a frequent delay in the diagnosis of prosthetic joint infection (PJI) and thus late treatment. This paper gives an update on the etiology, epidemiology, clinical presentation, and diagnosis of PJI. Emphasis is laid on the value of a multimodal approach to PJI treatment Р a combination of surgery and etiotropic antibiotic therapy. The choice of a treatment modality is determined by patient status, comorbidity, and the magnitude and duration of the infectious process.